Associations of weight-adjusted-waist index and depression with secondary infertility - Fei Sun; Min Liu; Shanshan Hu; Ruijie Xie; Huijuan Chen; Zhaona Sun; Huiya Bi (Frontiers in Endocrinology, 2024)
BackgroundObesity and psychological factors were identified as risk factors for female infertility. The study investigated the correlation between WWI, depression, and secondary infertility, focusing on the potential mediating role of depression.MethodsAccording to the data from NHANES, this cross-sectional study used multiple regression analysis, subgroup analysis, and smooth curve fitting to explore the relationship between WWI, depression, and secondary infertility. The diagnostic ability of WWI was evaluated and compared to other obesity indicators using the ROC curve. The mediating effect test adopted the distribution of the product.ResultsThis study involved 2778 participants, including 381 (13.7%) women with secondary infertility. Results showed that higher WWI (OR = 1.31; 95% CI, 1.11-1.56) and depression scores (OR = 1.03; 95% CI, 1.01-1.06) were associated with secondary infertility. There was a positive correlation between WWI and secondary infertility (nonlinear p = 0.8272) and this association was still consistent in subgroups (all P for interaction> 0.05). Compared with other obesity indicators, WWI (AUC = 0.588) also shows good predictive performance for secondary infertility. Mediation analysis showed that depression mediated the relationship between 3.94% of WWI and secondary infertility, with a confidence interval of Za * Zb excluding 0.ConclusionWWI exhibited a relatively good correlation in predicting secondary infertility than other obesity indicators, and depression may be a mediator between WWI and secondary infertility. Focusing on the potential mediating role of depression, the risk of secondary infertility due to obesity may be beneficially reduced in women.